Incised Bamboo from New Caledonia: A Visual Analysis - Burns, Margaret E. (The Australian journal of anthropology, 2002)
The intricate artwork that adorns bamboo artefacts from New Caledonia is made up of a restricted range of basic elements. By combining and recombining these elementary shapes—chevrons, triangles, pentagons—the artists have produced narratives of a potentially high documentary quality. Before these narratives can be incorporated into the history of the country, however, it is necessary that the polysemic richness of the visual motifs and their transfigurative power be understood. This article is a small step in that direction.